(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the essence of the principles of adapting phonological-rhythmic exercises in terms of speech defects from a scientific and pedagogical point of view. Phonologorhythmics is considered an effective speech therapy method that serves to develop speech activity in children through the combination of speech, movement, and rhythm elements. The importance of the principles of individual approach, differentiated approach, systematicity and consistency, and integrativity in the organization of phonological-rhythmic exercises has also been revealed.